Juvenile Idiopathic Arthritis Associated Uveitis. Current Status: Epidemiology, Pathogenesis, and Clinical Issues - Alexandr A. Yakovlev; Tatiana N. Nikitina; Mikhail M. Kostik (Вопросы современной педиатрии)
Uveitis is the most common extraarticular manifestation of juvenile idiopathic arthritis (JIA) and with no adequate management results in serious eye complications such as cataracts, secondary glaucoma, retinal detachment, and linear corneal dystrophy. This pathology reduces patients’ quality of life and can lead to significant social and economic losses, both due to direct health costs and due to disability (total loss of sight). Childhood uveitis accounts for approximately 5–10% of all uveitis in global population, however their prevalence has been increasing in recent years. The etiology and pathogenesis of JIA-associated uveitis remains poorly studied despite the well-known correlation of uveitis with JIA. Uveitis in children is difficult to diagnose in routine pediatric practice, both due to its course (asymptomatic/mild), and due to challenging verbal communication and examination (young children), which poses significant clinical problem. This article presents current data on the epidemiology, pathogenesis, clinical manifestations, and terminology of JIA-associated uveitis.